Reforms for more and better quality jobs in Spain - Jin, Yosuke (OECD Economics Department Working Papers, 2017)
The Spanish economy is growing strongly, but there is a risk that many people are being left behind. Unemployment, especially among young people and the low-skilled, remains very high. About half of all the unemployed have been unemployed for over a year and one third for more than two years. A quarter of all those who are employed are on temporary jobs. Since the global economic crisis, poverty and inequality have increased. An immediate priority is to ensure adequate income support for those most in need. Getting more people into better jobs is crucial to raise living standards and to reduce poverty. In terms of structural policies, this requires continuing to improve activation policies, such as training and job placement, re-skilling and up-skilling the unemployed, preventing youth from leaving the education system under-qualified and better on-the-job-training. More can be done to foster the creation of better quality jobs by reducing barriers to hiring and addressing labour market duality